PEMAKAIAN VARIASI BAHASA DALAM SPANDUK KAMPANYE PEMILU TAHUN 2014 DI KABUPATEN BANTUL - Ermawati Ermawati; Nusarini Nusarini (CARAKA, 2014)
Theaimofthisthesiswere(1)describingtheinfluencefactorsof languagevariationongeneralelection banners year2014inBantul(2)describing the useof persuasive technique on general election bannersyear 2014 inBantul. Thewriterusedscrutinizetechniquetogetthedata.Itwasdonewith scrutinizenorobservationtotheresearchareasfromMaret16,2014untilApril5, 2014.Then it was written onthedatacardanditwasclassifiedbasedonthe language variation of generalelection banners. The datas Â were taken about phrases, clauses, and sentencesthatwereonthelanguagevariationofgeneral electionbanners.Theresourcesofdata were fromgeneralelectionbannersthat outstretched in Bantul. The writer usedequalmethode with connect-appeal-distinguish techniqud to analyzethedata. The result of this researchshowed that (1) the influence Â factors of languagevariationongeneralelectionbannersyear2014inBantulwere(a)the settingandscene(the placeandthesituation)wereinBantul,(b)theparticipants (thetalkingparticipants)werefrom theyoungster,female,andmoslem,(c)the ends(thegoal)weretoinfluence, to ask,tu persueand toattemptthe reader,(d) instrumentalities(thetools)wereaboutwrittenlanguage,(e)normofinteraction (thetalkingnorm)werewrittenlanguagethatwas used.Bunchnormappreciated everxpoliticarparticipants,(f)genre(thekinds)werefromoftraditionalpoetry andwishes.(2)Persuasivetechniquethatwasusedinthewritingofbannerswere rasionalize, identification, suggestion, conformity,compensation and change.